Hubungan Pemilihan Material Struktur Baja, Beton Bertulang, dan Komposit dengan Kinerja Ekonomi Gudang Sepanjang Umur Rencana - Darmawan, Didit; Ridhoi, Muhammad Yusuf (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
This study examines how structural material selection for warehouses affects initial construction costs, load bearing capacity, and maintenance expenses over the building service life. Steel structures offer rapid erection and flexibility for future modifications but require corrosion and fire protection systems. Reinforced concrete provides high stiffness and impact resistance with lower maintenance costs in normal environments yet demands longer construction periods. Composite materials combine advantages of both steel and concrete but present inspection and repair challenges. Investment decisions should employ life cycle cost analysis with appropriate discount rates reflecting company capital costs and project risk profiles. Local property market preferences for specific material types influence resale values at the end of investment horizons. Companies with long term orientation and low capital costs tend toward concrete or high quality composite structures. Logistics startups needing fast operational commencement prefer steel structures despite higher maintenance expenses. No single material dominates all situations because project characteristics and corporate financial structures vary considerably.